SUPPLY CHAIN VEGETABLES PERFORMA WITH SUPPLY CHAIN OPERATIONAL REFERENCE (SCOR) MODEL - Dwi Putriana Nuramanah Kinding; Wahyu Budi Priatna; Lukman M. Baga (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2019)
The final objective of this research is the performance of vegetables supply chain in members to achieve the common goals of improvement the fulfillment of consumer need with best practice. The analytical method used is the Supply Chain Operational Reference (SCOR) models taking into the internal and external attributes of foodSCOR card. The five atributes used in this research is reliability, responsiveness, fleksibility, asset and cost. The result of measuring the performance of vegetables supply chain performa of the reliability, responsiveness and fleksibility attributes have achieved the superior performance position of foodSCOR card. Meanwhile, the value of vegetables supply chain performance on cost attribute of the total supply chain management cost (TCMC) and on reliability atrtributes of the order conformity performance with the standard only reaches a good position. But, the vegetables supply chain performance in the daily inventory attributes at the farm and commodity level, it only achieved an advantages level whereas at the level of corporate has reached the best performance (superior). This is because the company is trying to provide supplies according to demand to reduce storage costs, and this should be done by farmers as well.